Makna Lagu Masak Kopi yang di Populerkan Oesman pada Masyarakat Melayu di Bengkalis Provinsi Riau - M. Azam Alhadi; Idawati Idawati (Realisasi : Ilmu Pendidikan, Seni Rupa dan Desain, 2025)
This study aims to determine the meaning of the song masak kopi popularized by Oesman in the Malay community in Bengkalis, Riau Province. The theory used in this study is the theory (Barthes, 1968) by describing the meaning of denotation as the first level meaning and connotation as the second level meaning. Also supported by the theory of sociology by Schmitt. It is an action of a person or group of people when interacting with something outside themselves and understanding information about their environment which is obtained through sight, hearing, appreciation, feelings, and experience and interpretation. The method used in this research is descriptive qualitative. Data collection techniques in this study are observation, interviews and documentation. Data analysis techniques using data reduction, data presentation. Subjects in this study amounted to 4 people. The results of the research on the meaning of the masak kopi song in the Malay community in Bengkalis can be interpreted from 2 sides, namely from the music and from the lyrics. The Bengkalis Malay community interprets the music of the masak kopi song to reflect the characteristics of traditional Malay music which is very full of aesthetic and cultural values of the Malay community in Bengkalis, from the rhythm, melody and instruments used that strongly reflect the Malay identity of Bengkalis. The meaning of the lyrics can be concluded that the lyrics in the song masak kopi are related to the failure and fragility of love and hope caused by the influence of the establishment.